Dilemma of a Campus Company : Bakerâ€™s Best â€œSpreading Happinessâ€ - Bakhshi, Priti; Bhagwat, Jagdish (AMC Indian Journal of Entrepreneurship, 2019)
In the present scenario when start-ups are getting many facilities from the Indian government, it is better to promote the entrepreneurial environment in college itself. There are many campus companies running in good B-Schools and top engineering colleges where students are getting hands on experience of running a campus company. In this case, we made an attempt to understand the dilemmas of a campus company, where campus companies face the challenges of change in ownership and the challenge of scaling up a business.